Is it True That Production, Distribution and Government Policies Determine the Price of Rice in Southwest Aceh Regency: (Case Period 2010-2020) - Monalisa, Zainatun; Syahril, Syahril (Teunuleh Publisher, 2024)
This study aims to analyze the effect of rice production, rice distribution, and government policies on rice prices in Southwest Aceh Regency. The method used in this study is quantitative using time series data for the period 2010-2020. The results of this study indicate that partially the variables of rice production and distribution have a negative and insignificant effect on rice prices in Southwest Aceh Regency, while government policies (rice prices) have a positive and significant effect on rice prices in Southwest Aceh Regency. Then the results simultaneously prove that the variables of rice production, rice distribution, and government policies have a positive and significant effect on rice prices in Southwest Aceh Regency. This study suggests that efforts should be made to modernize agriculture, improve infrastructure such as bridges, roads and irrigation to increase production and smooth distribution, and the role of government policies in maintaining stable rice prices in Southwest Aceh Regency.